2020
DOI: 10.1002/ejoc.202001295
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine‐Mediated Styrene Hetero‐ and Homodimerization Initiation Proceeds with Two‐Electron Reductive Cleavage

Abstract: A mechanistic insight into the hetero‐ and homodimerizations (HETD and HOMD) of styrenes promoted by hypervalent iodine reagents (HVIRs; DMP and PIDA) and facilitated by hexafluoro2‐propanol (HFIP) to yield all‐trans cyclobutanes is reported using density functional theory (DFT) calculations. The initialization involving direct bimolecular one‐electron transfer is found to be highly unfavored, especially for the PIDA system. At this point, we suggest that the reaction is initiated with an overall two‐electron … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Additional exploration of the reaction mechanism focused on the initially proposed bimolecular single-electron reduction of the hypervalent iodine reagent, which was unfavored. Rather, the reaction is proposed to proceed via an overall two-electron reductive cleavage of two I–O bonds of DMP and PIDA to provide I­(III) (iodinane) and I­(I) (iodobenzene), respectively …”
Section: Hypervalent Iodine Chemistrymentioning
confidence: 99%
“…Additional exploration of the reaction mechanism focused on the initially proposed bimolecular single-electron reduction of the hypervalent iodine reagent, which was unfavored. Rather, the reaction is proposed to proceed via an overall two-electron reductive cleavage of two I–O bonds of DMP and PIDA to provide I­(III) (iodinane) and I­(I) (iodobenzene), respectively …”
Section: Hypervalent Iodine Chemistrymentioning
confidence: 99%
“…It has long been reported that electron-rich π systems such as methoxy aryls can donate an electron to PIFA through SET. ,, Similarly, trans-anethole ( 13 ) has been shown to dimerize when reacted with PIDA and the mechanism is said to proceed via the formation of a radical cation . Upon mixing of trans-anethole with PIDA in HFIP, we observed the characteristic signal of its radical cation form ( 14 ) at λ max of 390 and 600 nm (Figure ).…”
Section: Resultsmentioning
confidence: 78%
“…3,22,23 Similarly, transanethole (13) has been shown to dimerize when reacted with PIDA and the mechanism is said to proceed via the formation of a radical cation. 24 Upon mixing of trans-anethole with PIDA in HFIP, we observed the characteristic signal of its radical cation form (14) at λ max of 390 and 600 nm (Figure 4). 25 This is another clear demonstration of a SET pathway for methoxycontaining aromatics since trans-anethole cannot bind to PIDA via ligand exchange as do phenols.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, hexafluoroisopropanol (HFIP) was used experimentally, so we were keen to check whether changing to this solvent had a significant effect on our results. Using published SMD parameters for HFIP, [40] we recomputed free energies for the CMD C−H insertion step for our three templates (Figure 6). Using HFIP does not lower the overall barriers for C−H insertion or change their ordering.…”
Section: Resultsmentioning
confidence: 99%